The Impact of an Undergraduate Biology Class on Donor Recruitment at a Hospital-Based Blood Donor Center. Issue 3 (30th November 2019) - Peedin, Alexis R; Park, Yara A; Mazepa, Marshall A; Siniard, R Chad; Neish, Thomas; Raval, Jay S
Abstract: Objectives: A biology class, BIOL 294H, taught undergraduates about platelet donation while partnering with the University of North Carolina's (UNC's) hospital-based Blood Donation Center to recruit apheresis platelet donors. We identified our platelet donors' demographics and learned how BIOL 294H affected recruitment. Methods: Every platelet donor presenting to the UNC Blood Donation Center from February 7, 2017, to March 10, 2017, was asked to complete an electronic 10-question survey. Results: A total of 159 unique donors completed the survey; 64% were female and 75% were between ages 18 and 25 years. Overall, 70% were UNC undergraduate students. Over half (56%) reported first learning about platelet donation through word of mouth, and 22% cited specific efforts associated with BIOL 294H. Conclusions: Recruitment of undergraduate platelet donors primarily included BIOL 294H peer interactions and deliverables from the class, such as social media updates and events on campus. The sustained recruiting efforts of our students over many years contributed to recruitment of a majority of our platelet donors.